A1.32 The role of hematopoietic stem cells (HSC) in systemic autoimmunity. (13th February 2015) - Grigoriou, M; Verginis, P; Bertsias, G; Boumpas, DT; Banos, A
Abstract : Background and objectives: HSCs represent a cell population that gives rise to every lineage of blood cells, including granulocytes, lymphocytes, monocytes and endothelial cells, all of which have been implicated in the pathogenesis of Systemic Lupus Erythematosus (SLE). Although HSCs are thought to exist in a dormant state in bone marrow niche, recent evidence suggest that in lupus mice they over proliferate due to both intrinsic and extrinsic effects. Whether such alteration in the HSC compartment contributes to lupus pathogenesis, remains elusive. Furthermore, the molecular identity of this cell type after the inflammatory impact is unknown. Our working hypothesis is that the fundamental immune aberrations in SLE –genetic or epigenetic- may be easier to be traced back to the HSC population. Materials and methods: Hematopoietic stem cell progenitors were isolated from either healthy or NZB x NZW F1 lupus prone mice bone marrow. The selection markers used are Lin - Sca-1 + c-Kit + (LSK) cells, including long and short term HSCs. Cell sorting of the aforementioned populations was performed for enumeration and RNA extraction. RNA-seq analysis was performed. Results: Significantly increased frequencies as well as absolute numbers of HSCs were observed in the BM of lupus mice with established disease as compared to young NZB x NZW F1 mice or to C57/BL6 control mice. Importantly, our results show that bone marrow populations such as HSPCs, lymphoid and myeloid lineages seem to differ in homogeneity, correlating with either age or disease, indicating an alteration in HSC potential under inflammatory conditions. In depth bioinformatics analysis of the RNA-seq results of HSCs is in process. Conclusions: Our results will characterise the global gene expression of HSCs originating by lupus mice. Simultaneously, we plan to map SNPs in the genetic background of lupus mice and pinpoint the important ones for HSCs integrity. Acquired knowledge will provide insights into the contribution of HSC in lupus pathogenesis as well as will demonstrate how the respective environment could shape the HSC compartment function.